Ethno-religious conflict in Nigeria : a case study of Tafawa Balewa (1991-2011) - Suleiman, Ibrahim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The purpose of this study is to examine the factors that contribute to ethno-religious conflict in the Tafawa Balewa local government area of Bauchi state Nigeria, from 1991 to 2011. The thesis also examines the effect of conflict on the political and economic development and why attempts to resolve the conflict have been ineffective. The study uses manipulation by elites, socio-economic factors and communal identity as independent variables, whereas, ethno-religious conflict is the dependent variable. The analysis in the study is based on Smith's instrumental theory and Azar's protracted social conflict theory. The analysis of data utilises a mixed method i.e. quantitative and qualitative. Data collection included a survey using 30 close ended questions and involved 231 respondents. Interviews were conducted to complement the data collected from the questionnaires. Accordingly, descriptive statistics, factor analysis and multiple regressions were used in testing and analysing the data. The results of the findings show that socio-economic factors, political manipulation and communal identity are important factors that contributed to the conflict in Tafawa Balewa. Moreover, the conflict affects the socio-economic activities of the people and failure to implement the recommendations by special resolution committees has remained an obstacle in resolving the conflict.